Neck lymph node status on survival of regionally recurrent or persistent nasopharyngeal carcinoma - David C. M. Yeung (Nature Portfolio, 2020)
Abstract The aim of this study was to evaluate the impact of lymph node status from neck dissection pathological specimens on the survival for isolated regional nodal recurrence or persistence after primary treatment of nasopharyngeal carcinoma. Through a retrospective cohort study performed in an academic tertiary referral hospital in Hong Kong. Forty-six patients who underwent a salvage neck dissection between June 2001 and January 2013 for isolated regionally recurrent or persistent nasopharyngeal carcinoma was performed. Informed consent was waived for this retrospective study by The Joint CUHK-NTEC CREC. In the study forty-six patients had a salvage neck dissection for nodal failure with a mean age of 53 and 74% (34) were male. With a mean follow-up of 45.3 months, Overall survival, disease specific survival, loco-regional recurrence free survival, and regional recurrence free survival were 56.5%, 73.9%, 87.0%, and 91.3% respectively. For both univariate and multivariate analysis, patients with a number of positive lymph nodes more than 5 and a lymph node density more than 20% were significantly associated with poorer overall survival. Extracapsular spread and pathological cervical lymph node staging did not have an association with poorer survival. In conclusion, an absolute number of positive lymph nodes more than five and a lymph node density more than 20% were potentially useful prognostic factors affecting survival following a neck dissection for regional residual or recurrent nasopharyngeal carcinoma.